Modifying the electrical excitability of cardiomyocytes in rainbow trout (Oncorhynchus mykiss) through exercise training - Le; Thuy Thi Ngoc; Seppänen, Eila; Haverinen, Jaakko; Anttila, Katja (American Physiological Society, 2026)
Exercise training is known to improve the function of the heart in fish. However, at cellular level the mechanisms for improvements are still largely unknown. Therefore, we aimed to investigate the impact of exercise training on electric excitation of cardiac contraction in ventricle myocytes of rainbow trout (Oncorhynchus mykiss) through the investigation of sodium (INa), L-type calcium (ICaL), delayed and inward rectifier potassium (IKr and IK1) currents and action potential (AP) characteristics. The fish were divided into untrained (control) and trained groups. Control fish were kept in standard holding tanks with a water flow rate of 0.3 body lengths per second (bl s-1), while trained fish experienced daily sessions of exercise for 6 hours, five days a week, for a period of 4 weeks, at a water flow rate of 0.9 bl s-1. The patch clamp technique was used to compare ion currents between groups. Trained fish exhibited higher whole-cell capacitance, consistent with an increased membrane surface area of ventricular myocytes. Furthermore, exercise training led to reduced current densities of INa, ICaL and outward IK1. These changes in currents were connected to marked alterations in AP morphology, including depolarized resting membrane potential (RMP), depolarized threshold potential (TP), and prolonged AP at 90 % repolarization (APD90). In summary, this study presents novel evidence that swimming exercise training can impact the ventricular ion currents which leads to prolongation of the action potential and that the cardiomyocytes of the rainbow trout are highly plastic, enabling them to respond to changes in the environment.